2015
DOI: 10.2136/sh14-11-0014
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Changes in Sandy Soils under Intensive Agriculture in Wisconsin

Abstract: We have quantified the effect of land use change by measuring soil physiochemical changes in sandy soils under intensive agriculture, grasslands, and pine forest in the central sands plain of Wisconsin, USA. The soils under agriculture (corn, potato, soybeans, and peas) are irrigated (280 mm yr–1), limed, fertilized, and leveled. Soil observations were made in 82 pedons, and soil horizons, texture, and pH were measured. The soils are all very sandy and somewhat excessively drained. In all pedons, sand percent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Kristiansen [36] and Zhang et al [50] found that Fe2O3 was highest in the Bt horizon due to an increase in clay and soil carbon content. Goethite was the only Fe oxide present in the diffractograms for the soil under forest, but other studies have showed that these sandy soils may contain up to 12% feldspars and less than 3% Fe oxides, inosilicates (augite), and silicates (hornblende) [22].…”
Section: Elements Mineralogy and Weatheringmentioning
confidence: 91%
See 3 more Smart Citations
“…Kristiansen [36] and Zhang et al [50] found that Fe2O3 was highest in the Bt horizon due to an increase in clay and soil carbon content. Goethite was the only Fe oxide present in the diffractograms for the soil under forest, but other studies have showed that these sandy soils may contain up to 12% feldspars and less than 3% Fe oxides, inosilicates (augite), and silicates (hornblende) [22].…”
Section: Elements Mineralogy and Weatheringmentioning
confidence: 91%
“…In these sandy soils, quartz was the dominant mineral, and Si was high throughout the soil profiles (191-297 g Si kg −1 ). Madison and Lee [22] found that up to 96% of these sandy soils are quartz dominant. The Bt horizons had low Si (191-224 g Si kg −1 ), and a slightly higher silt and clay content (100-190 g kg −1 ) than the Ap horizons.…”
Section: Elements Mineralogy and Weatheringmentioning
confidence: 99%
See 2 more Smart Citations